2010
DOI: 10.3233/mgc-2010-0011
|View full text |Cite
|
Sign up to set email alerts
|

Potassium cation exchange with "crowned" indium(I) trifluoromethanesulfonate

Abstract: The treatment of the soluble indium(I) salt [In([18]crown-6)][O3SCF3] with several potassium salts of the form [K][A] results in the release of the indium(I) cation from the crown ether and the production of salts of [K([18]crown-6)] + and uncomplexed [In] + .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Cooper and Macdonald demonstrated that is it possible to displace the indium(I) ion from [18]crown-6 with a potassium ion. 179 For example, the treatment of solutions of the very soluble [In( [18]crown-6)][OTf] complex with KX (X = Cl, Br, I), results in the immediate formation of finely dispersed powders of InX. Such finely dispersed indium(I) halides may have practical applications in synthetic applications given the insolubility and instability of the bulk indium(I) halide salts.…”
Section: Indium(i)mentioning
confidence: 99%
“…Cooper and Macdonald demonstrated that is it possible to displace the indium(I) ion from [18]crown-6 with a potassium ion. 179 For example, the treatment of solutions of the very soluble [In( [18]crown-6)][OTf] complex with KX (X = Cl, Br, I), results in the immediate formation of finely dispersed powders of InX. Such finely dispersed indium(I) halides may have practical applications in synthetic applications given the insolubility and instability of the bulk indium(I) halide salts.…”
Section: Indium(i)mentioning
confidence: 99%
“…77 Treatment of [In(18-crown-6)]-[O 3 SCF 3 ] with several potassium salts has resulted in the release of the indium(I) cation from the crown ether and the production of salts of [K(18-crown-6)] + and uncomplexed [In] + . 78 A fluoro-metallocrown has been found to bind caesium, extracting it from aqueous solutions into an organic layer. 79 A calix-4-arene-calix-4-pyrrole, a receptor with three different caesium recognition modes has been described.…”
Section: Sodium Potassium Rubidium and Caesiummentioning
confidence: 99%